(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
The present review article deals with the utility of microscope in a forensic science and its utility in research and investigation. The review article tries to explain the basic of microscopes ranging from a simple microscope to electron microscope. It further explains the utility of microscopes in a multitude of areas that could ease investigation and research in a forensic science laboratory.